Cosmopolitanism 'from below' and claim-making in the Global South. Issue 1 (2nd January 2023) - Mushonga, Rufaro Hamish; Dzingirai, Vupenyu
ABSTRACT: The increased presence of migrant entrepreneurs in Downtown, Harare has been met with ambivalence and suspicion. As Zimbabwean nationals forge a 'new nationalism', they confront migrant populations in their midst making claims to the very urban spaces and territories on which their lives and livelihoods are anchored. Using ethnographic inquiry among Nigerian entrepreneurs in Harare, the article explores how this specific migrant population draws on varied and often competing systems of cosmopolitan tactics (e.g. religion, human rights rhetoric and Pan-Africanism) to position themselves in the spaces and networks needed to achieve pragmatic goals. Through these cosmopolitan tactics, migrants view places as inherently heterogeneous, interdependent and interconnected through global flows of people, capital and information rather than demarcated into mutually bounded and exclusive entities. In so doing, the article offers a vivid case study of the transformative power of cosmopolitanism 'from below' within urban spaces, where diversity and innovation intersect.